Meningkatkan Aktivitas Dan Hasil Belajar Menggunakan Model Papeda Pada Kelas V SD - Raudatun Inayah; Herti Prastitasari (CV. ITTC INDONESIA, 2023)
The problem in this study is the low activity and learning outcomes. The purpose of this research is to describe teacher activities, analyze student activities in the learning process, and analyze learning outcomes. This research uses a qualitative approach with the type of Classroom Action Research. Data analysis techniques in this study were obtained through written test techniques and observation sheets. The results of this study indicate that teacher activity at meeting I only achieved a score of 20 at meeting 4 increased to 28, then student activity increased, which at meeting I only reached 45% at meeting IV increased to 100%. The classical completeness of learning outcomes at the first meeting only reached 55% and increased at the fourth meeting to 100%. Based on the results of this study it can be concluded that the use of the PAPEDA model can increase activity and learning outcomes. As for suggestions for school principals, teachers and other researchers is to provide guidance and coaching in implementing innovative learning models as an effort to improve the quality of classroom learning and references to help write scientific papers.